Improved Performance Of DTC Of Five-Phase Induction Machines - Lourdes Victor Raj, Logan Raj; Jidin, Auzani; Che Wan Mohd Zalani, Che Wan Mohd Faizal; Abdul Karim, Kasrul; Goh, Wee Yen; Jopri, Mohd Hatta (2013)
The paper describes about optimal voltage vector selection for high-performance of Direct Torque Control (DTC) of five-phase induction machine. The de-coupled control of stator flux and electromagnetic torque based on hysteresis controllers as employed in conventional DTC is applied to retain the simplicity and to provide quick instantaneous control. A look-up table that selects the most optimal voltage vectors according to the speed operations, i.e. low-speed, middle-speed and high-speed is proposed to improve DTC performances such as excellent torque dynamic control, minimization of torque ripple, high-efficiency (due to lower switching frequency) and extension of constant torque region. All the improvements are validated through simulation results.